Phytochemical Investigation, TLC-HPLC Fingerprinting and Antioxidant Activity of Cissus repanda Roots - SachinBhusari, SachinBhusari; KanchanNikam, KanchanNikam; BhanudasKuchekar, BhanudasKuchekar; PravinWakte, PravinWakte (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: To perform phytochemical screening, TLC, HPLC fingerprinting and antioxidant assay of Aqueous, Aqueous-Ethanolic and 95% Ethanolic extracts of Cissus repanda roots. Methods: Aqueous, Aqueous-Ethanolic and 95% Ethanolic extracts of Cissus repanda roots were subjected to preliminary phytochemical analysis. TLC patterns of all the three extracts were developed on the basis of phytochemical analysis results. All extracts were subjected to HPLC fingerprinting. The antioxidant potential of all the three extracts of Cissus repanda roots were evaluated by DPPH scavenging assay. Results: All three extracts showed the presence of various phytochemicals belonging to different chemical class viz. Alkaloid, glycosides, tannins, flavonoids, steroids and polyphenols. TLC fingerprinting of aqueous extracts showed presence of one distinct phytochemical with Rf value of 0.07 while Aqueous-Ethanolic extract showed three phytochemicals with Rf values of 0.11, 0.55, 0.95 and 95% Ethanolic extract showed two phytochemicals with Rf values of 0.16, 0.71. HPLC fingerprints of all extract showed four prominent peaks. Compounds showing peaks at 48.48 and 67.41 min. were found to be around 21.6 and 19.2 % in the extract. All the extracts were subjected to antioxidant activity. Alcoholic extract of Cissus repanda roots showed highest antioxidant activity of 72.02 % whereas Aqueous extract and Aqueous-Ethanolic extract showed 61.66 and 40.47 % antioxidant activity respectively. Conclusion: The present study provides qualitative phytochemical analysis and antioxidant potential of Cissus repanda root extracts. HPLC and TLC fingerprint would be useful identification and isolation of therapeutically important phytochemicals. All extracts of Cissus repanda root showed good antioxidant activity.
Keywords: Antioxidant assay; Cissus repanda; HPLC; Phytochemical analysis; Thin; Layer Chromatography